Benefits of atomic-level processing by quasi-ALE and ALD technique. (16th May 2017) - Honda, M; Katsunuma, T; Tabata, M; Tsuji, A; Oishi, T; Hisamatsu, T; Ogawa, S; Kihara, Y
Abstract: A new technology has been developed using the atomic layer etching (ALE) and atomic layer deposition (ALD) concepts. It has been applied to self-aligned contacts (SAC) and patterning processes, for the sub 7 nm technology generation. In the SAC process, ultra-high selectivity of SiO2 etching towards SiN is required, for which we have developed quasi-ALE technique for SiO2 etching. We were able to significantly improve the trade-off between the etching ability of SiO2 on the micro slit portions and SiN selectivity. Quasi-ALE precisely controls the reaction layer thickness of the surface, by controlling the radical flux and ion flux independently, and hence enables etching at lower ion energies ( E i < 250 eV). On the other hand, in the patterning processes, the shrinking of critical dimensions (CD) without loading is mandatory. Therefore, we developed a new process flow that combines ALD technique and etching. With this method, we were able to achieve CD shrinking at atomic-layer level precision for various patterns, without causing CD loading. In addition, we were also able to uniformly control the CD shrinkage amount across the whole wafer. This is because this technique takes advantage of the deposition step which is independent of the pattern density and the location on the wafer by self-limited reactions.